Collaborative Governance in Tourism Sector Development (A Comparative Study in Jayapura City and Selayar Islands Regency) - Agustinus Fatem; Yosephina Ohoiwutun; Ilham; Febi Lisa Koridama (urn:multiple://2988-7828multiple.v3i84)
This study aims to analyze and compare the application of Collaborative Governance in the development of the tourism sector in Jayapura City and Selayar Islands Regency. Both regions represent island characteristics with complex governance challenges, such as infrastructure limitations, diversity of actors, and environmental vulnerability. This study employs a library research approach using a descriptive-comparative method based on qualitative analysis. Data were obtained from various secondary sources, such as journal articles, policy documents, scientific proceedings, and official government websites. The analytical framework is based on the theory of Collaborative Governance, which is broken down into twelve indicators of collaborative governance. The results of the analysis show that Jayapura City excels in the involvement of indigenous communities, village deliberation mechanisms, and community-based leadership, despite facing challenges in cross-sector coordination and participatory evaluation. In contrast, Selayar Islands Regency excels in formal institutional aspects, regulatory strengthening, and the role of local actors such as Pokdarwis (tourism awareness group), but is still top-down in its collaboration process. This study concludes that the effectiveness of Collaborative Governance is determined by the suitability of the approach to the local social and institutional context. Strategic recommendations include strengthening collaborative forums, participatory evaluation, and integrating cultural values into tourism policy design.